2017
DOI: 10.1371/journal.pone.0180853
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation dependent mTORC1 signaling interferes with the switch from keratinocyte proliferation to differentiation

Abstract: Psoriasis is a frequent and often severe inflammatory skin disease, characterized by altered epidermal homeostasis. Since we found previously that Akt/mTOR signaling is hyperactivated in psoriatic skin, we aimed at elucidating the role of aberrant mTORC1 signaling in this disease. We found that under healthy conditions mTOR signaling was shut off when keratinocytes switch from proliferation to terminal differentiation. Inflammatory cytokines (IL-1β, IL-17A, TNF-α) induced aberrant mTOR activity which led to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 43 publications
3
60
1
1
Order By: Relevance
“…39 Its aberrant induction is mediated by proinflammatory cytokines, such as IL-1b, IL-17A, and TNF-a, increasing proliferation and reducing expression of differentiation markers. 40 Our results indicate that LAT1 expression in keratinocytes is not essential for control of keratinocyte proliferation, indicating a functional compensation with alternative amino acid transporters, such as LAT2 or LAT3, which are also expressed in the epidermal layer in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 66%
“…39 Its aberrant induction is mediated by proinflammatory cytokines, such as IL-1b, IL-17A, and TNF-a, increasing proliferation and reducing expression of differentiation markers. 40 Our results indicate that LAT1 expression in keratinocytes is not essential for control of keratinocyte proliferation, indicating a functional compensation with alternative amino acid transporters, such as LAT2 or LAT3, which are also expressed in the epidermal layer in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 66%
“…There are two mTOR complexes: mTORC1, which controls protein metabolism [36] ; and mTORC2, which activates AKT signalling. [37] We and others have shown that mTORC1 and mTORC2 activity is present in suprabasal layers of the epidermis [38][39][40] with mTORC1 activity, measured by S6 phosphorylation, concentrated in the granular layer of in vitro skin models. [38,39] mTORC1 and mTORC2 complexes contain the subunits Raptor and Rictor, respectively, [41] and selective deficiency of these subunits allows manipulation of mTORC1 and mTORC2 activity to dissect their roles in the epidermis.…”
Section: Akt Kinases and Their Regulationmentioning
confidence: 99%
“…To our knowledge, we are the first to replicate these results with platelet releasate on NHEKs and HaCaTs. Typical keratinocyte differentiation involves an increase in cell density (Buerger et al, ). Further to this, the observed morphological differences between platelet releasate and growth media on the inhibition of proliferation in high density keratinocyte populations support the lineage progression results, exiting the cell cycle faster and upregulating terminal differentiation genes greater than normal culture conditions.…”
Section: Discussionmentioning
confidence: 99%